Pengembangan Modul Pembelajaran Tematik Tema 7 Subtema 1 Kelas V Sekolah Dasar Negeri 2 Sawah Brebes Tahun Pelajaran 2021/2022 - Dini, Rahma; Jaya, Wayan Satria; Harjanto, Ambyah; Anindito, Filardi (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This research aims to produce thematic learning modules as valid additional teaching materials and to khow both the theacher’s response and the learner’s response to synthesize in learning. The modules used in this study are ADDIE to improve from Borg and Gall. type Research and Development (R&D), consisting of the five stage is Analysis, Design, Development, Implementation, and Evaluation. The intrument used in the data-collection process are kuisioner, interview, and documentataries. The validity and student response test uses the established and to lknow the teacher’s responses uses the interview desribed by descriptive explanation. The study is carried out in the grade V of elemenstary school 2 Sawah Brebes. This produced a product that was declared valid and received a value of 96,25% form materials experts, 88% of linguistisc and 84,61% if design expert. Student responsesn are at a rate of 90% of high ability, 94% of modesrate talent students, and 96% of lower talent students, while getting adequate responses from teachers because product can make learning easier.